Stress and Corticosteroids Modulate Muscarinic Long Term Potentiation (mLTP) in the Hippocampus - Shavit Stein, Efrat; Itsekson Hayosh, Ze’Ev; Vlachos, Andreas; Maggio, Nicola (Frontiers in Cellular Neuroscience, 2017)
Stress influences synaptic plasticity, learning and memory in a steroid hormone receptor dependent manner. Based on these findings it has been proposed that stress could be a major risk factor for the development of cognitive decline and dementia. Interestingly, evidence has been provided that stress also affects muscarinic, i.e., acetylcholine (ACh)-mediated neurotransmission. To learn more about the impact of stress and steroids on synaptic plasticity, in this study, we investigated the effects of stress on muscarinic LTP (mLTP). We report that multiple, unpredictable exposure to stress depresses carbachol (0.5 µM)-induced mLTP, while this effect of stress is not observed in hippocampal slices prepared from mice exposed only to a single stressful procedure. Furthermore, we demonstrate that activation of distinct steroid hormone receptors is involved in stress-mediated alterations of mLTP. Activation of mineralocorticoid receptors (MR) promotes mLTP, while glucocorticoid receptor (MR) activity impairs mLTP. These effects of multiple unpredictable stress on mLTP are long-lasting since they are detected even two weeks after the last stressful experience. Thus, multiple unpredictable events rather than a single stressful experience affect mLTP in a steroid hormone receptor dependent manner, suggesting that chronic unpredictable stress can lead to lasting alterations in hippocampal cholinergic plasticity.